Identifikasi Kandungan Logam Berat Kadmium (Cd) pada Lumpur Sawah dan Beras (Oryza sativa L.) dari Lahan Sawah di Sekitar Perairan Danau Limboto - Agung Nurwahid Mancu; Herlina Jusuf; Tri Septian Maksum (Transbahasa, 2026)
Limboto Lake is a critically threatened lake experiencing declining environmental quality due to sedimentation and heavy metal contamination, including cadmium (Cd). This study aims to identify the Cd content in paddy soil and rice from agricultural fields surrounding the Limboto Lake watershed. This research employed a descriptive quantitative approach conducted at three stations (Bolihuangga, Hunggaluwa, and Dutulanaa). Sampling was carried out using a composite method to ensure field-representative data, followed by Cd analysis by Atomic Absorption Spectrophotometry (AAS). The results showed that Cd was detected in all paddy soil samples, with the highest to lowest concentrations found at Bolihuangga Station (0.29 ppm), Hunggaluwa Station (0.24 ppm), and Dutulanaa Station (0.23 ppm), respectively, all of which remained below the CCME quality standard of 0.6 ppm. In the rice samples, Cd was also detected, with the highest concentrations at Hunggaluwa Station (0.0024 mg/kg), followed by Bolihuangga (0.0020 mg/kg) and Dutulanaa (0.0019 mg/kg), all of which complied with the SNI 6128:2020 standard of 0.1 mg/kg. Although these levels are below the permissible thresholds, the presence of Cd indicates that heavy metals are entering the food chain. Given the persistent and bioaccumulative nature of Cd, this heavy metal will continue to accumulate in the environment and build up in body tissues. Regular environmental monitoring is required. It is recommended that communities and farmers reduce the excessive use of phosphatased chemical fertilizers and transition to organic fertilizers or to more sly friendly agricultural methods to prevent long-term accumulation of hebemetilsan paddy fields.